Microsites as Low-Cost Learning Management Systems: A Policy Analysis of Device Management in Indonesian Elementary Education - Apremedian Apremedian; Fatimah Fatimah; Moh Nurkhasan; Ratna Kusuma Ningrum; Nurkolis Nurkolis (Journal of Innovation and Research in Primary Education, 2026)
The rapid digitization of education demands accessible tools for managing learning devices in elementary schools. This study examines the implementation, effectiveness, and influence of teacher and student digital competence on microsite utilization as a low-cost solution for centralized learning device management at SD Negeri 4 Kuwaron. A qualitative single-case study design was employed. Data were collected through semi-structured interviews with seven teachers, the principal, and five students, supplemented by 12 hours of non-participant classroom observations and systematic documentation analysis of the school’s s.id microsite. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña with triangulation for trustworthiness. Microsites functioned primarily as centralized administrative repositories (66% static documents), delivering notable time savings and ease of access for teachers and enabling principal monitoring. Pedagogical features (interactive Quizizz embeds) were used in only 25% of observed lessons and exclusively by teachers with higher digital competence. Student access limitations led to deliberate low-bandwidth content adaptations. An unexpected finding was the emergence of access-log monitoring for informal home learning oversight. The findings strongly support Rogers’ Diffusion of Innovations theory (relative advantage and compatibility) and the TPACK framework, while highlighting a staged adoption process in low-resource settings. Microsites serve as effective, scalable proxies for formal Learning Management Systems, offering practical implications for Merdeka Curriculum implementation despite infrastructure constraints.